Analysis of pedagogical practices in physical education with children with disabilities in the context of early childhood education: An integrative review - Paulo Sergio Avelino dos Santos; Ricardo de Almeida Pimenta; Rodrigo Lema Del Rio Martins (Universidade Federal do Norte do Tocantins, 2023)
The inclusion of children with disabilities in basic education has long been a topic of discussion within society. Marked by an exclusionary, segregational past, and considered trainable based on the preparatory-sports concepts of physical education, children have been gaining their space as subjects of rights and protagonists in their learning process. Thus, this study aims to analyze how scientific articles characterize the pedagogical work of physical education with children with disabilities within early childhood education. For this, an integrative review was carried out using the Redalyc database and the Capes Periodicals Portal, limited to the Scopus and Scielo databases. After applying the inclusion criteria, nine articles were selected. The productions point out possibilities for inclusion, such as collaborative work between teachers and families, play and games as a strategy to promote interaction between children, and university extension as a path to solidify initial formation. Thus, it can be concluded that the analyzed scientific articles recognize the importance of an inclusive approach in early childhood physical education, valuing the active and autonomous participation of children with disabilities in the learning process.